Upregulated glycolysis correlates with tumor progression and immune evasion in head and neck squamous cell carcinoma - Hideyuki Takahashi (Nature Portfolio, 2021)
Abstract Altered metabolism is an emerging hallmark of cancer. Cancer cells preferentially utilize glycolysis for energy production, termed “aerobic glycolysis.” In this study, we performed a comprehensive analysis of the glycolytic activity in head and neck squamous cell carcinoma (HNSCC) using data obtained from The Cancer Genome Atlas database. We first divided 520 patients with HNSCC into four groups based on the mRNA expression of 16 glycolysis-related genes. The upregulated glycolytic activity positively correlated with human papillomavirus-negative tumor type, advanced T factor, and unfavorable prognosis. The gene set enrichment analysis revealed upregulation of several hallmark pathways, including interferon-alpha response, myc targets, unfolded protein response, transforming growth factor-β signaling, cholesterol homeostasis, and interleukin 6-Janus kinase-signal transducer and activator of transcription 3 signaling, in the glycolysis-upregulated groups. Immune cell enrichment analysis revealed decreased infiltration of T cells, dendritic cells, and B cells in the glycolysis-upregulated groups, suggesting impaired tumor antigen presentation, T cell activation, and antibody production in the TME. Moreover, the expression profile of immune-related genes indicated increased immune evasion in the glycolysis-upregulated tumors. Collectively, these findings suggest that transcriptome analysis of glycolytic activity of tumors has the potential as a biomarker for tumor progression and immunological status in patients with HNSCC.